MicroRNA156: a potential graft-transmissible microrna that modulates plant architecture and tuberization in solanum tuberosum ssp andigena - Bhogale, Sneha; Mahajan, Ameya S.; Natarajan, Bhavani; Rajabhoj, Mohit; Thulasiram, Hirekodathakallu V.; Banerjee, Anjan K. (Plant Physiology, 2014)
MicroRNA156 (miR156) functions in maintaining the juvenile phase in plants. However, the mobility of this microRNA has not been demonstrated. So far, only three microRNAs, miR399, miR395, and miR172, have been shown to be mobile. We demonstrate here that miR156 is a potential graft-transmissible signal that affects plant architecture and tuberization in potato (Solanum tuberosum). Under tuber-noninductive (long-day) conditions, miR156 shows higher abundance in leaves and stems, whereas an increase in abundance of miR156 has been observed in stolons under tuber-inductive (short-day) conditions, indicative of a photoperiodic control. Detection of miR156 in phloem cells of wild-type plants and mobility assays in heterografts suggest that miR156 is a graft-transmissible signal. This movement was correlated with changes in leaf morphology and longer trichomes in leaves. Overexpression of miR156 in potato caused a drastic phenotype resulting in altered plant architecture and reduced tuber yield. miR156 overexpression plants also exhibited altered levels of cytokinin and strigolactone along with increased levels of LONELY GUY1 and StCyclin D3.1 transcripts as compared with wild-type plants. RNA ligase-mediated rapid amplification of complementary DNA ends analysis validated SQUAMOSA PROMOTER BINDING-LIKE3 (StSPL3), StSPL6, StSPL9, StSPL13, and StLIGULELESS1 as targets of miR156. Gel-shift assays indicate the regulation of miR172 by miR156 through StSPL9. miR156-resistant SPL9 overexpression lines exhibited increased miR172 levels under a short-day photoperiod, supporting miR172 regulation via the miR156-SPL9 module. Overall, our results strongly suggest that miR156 is a phloem-mobile signal regulating potato development.

MiRNA160 is associated with local defense and systemic acquired resistance against Phytophthora infestans infection in potato - Natarajan, Bhavani; Kalsi, Harpreet S.; Godbole, Prajakta; Malankar, Nilam; Thiagarayaselvam, Aarthy; Siddappa, Sundaresha; Thulasiram, Hirekodathakallu V.; Chakrabarti, Swarup K.; Banerjee, Anjan K. (Journal of Experimental Botany, 2018)
To combat pathogen infection, plants employ local defenses in infected sites and elicit systemic acquired resistance (SAR) in distant tissues. MicroRNAs have been shown to play a significant role in local defense, but their association with SAR is unknown. In addition, no such studies of the interaction between potato and Phytophthora infestans have been reported. We investigated the role of miR160 in local and SAR responses to P. infestans infection in potato. Expression analysis revealed induced levels of miR160 in both local and systemic leaves of infected wild-type plants. miR160 overexpression and knockdown plants exhibited increased susceptibility to infection, suggesting that miR160 levels equivalent to those of wild-type plants may be necessary for mounting local defense responses. Additionally, miR160 knockdown lines failed to elicit SAR, and grafting assays indicated that miR160 is required in both local and systemic leaves to trigger SAR. Consistently, SAR-associated signals and genes were dysregulated in miR160 knockdown lines. Furthermore, analysis of the expression of defense and auxin pathway genes and direct regulation of StGH3.6, a mediator of salicylic acid-auxin cross-talk, by the miR160 target StARF10 revealed the involvement of miR160 in antagonistic cross-talk between salicylic acid-mediated defense and auxin-mediated growth pathways. Overall, our study demonstrates that miR160 plays a crucial role in local defense and SAR responses during the interaction between potato and P. infestans.
Keywords: Auxin-salicylic acid antagonism; microRNA; miR160; Phytophthora infestans; Solanum chacoense; Solanum tuberosum; systemic acquired resistance

Development of aerial and belowground tubers in potato is governed by photoperiod and epigenetic mechanism - Kondhare, Kirtikumar R.; Kumar, Amit; Patil, Nikita S.; Malankar, Nilam N.; Saha, Kishan; Banerjee, Anjan K. (Plant Physiology, 2021)
Plants exhibit diverse developmental plasticity and modulate growth responses under various environmental conditions. Potato (Solanum tuberosum), a modified stem and an important food crop, serves as a substantial portion of the world's subsistence food supply. In the past two decades, crucial molecular signals have been identified that govern the tuberization (potato development) mechanism. Interestingly, microRNA156 overexpression in potato provided the first evidence for induction of profuse aerial stolons and tubers from axillary meristems under short-day (SD) photoperiod. A similar phenotype was noticed for overexpression of epigenetic modifiers-MUTICOPY SUPRESSOR OF IRA1 (StMSI1) or ENAHNCER OF ZESTE 2 (StE[z]2), and knockdown of B-CELL-SPECIFIC MOLONEY MURINE LEUKEMIA VIRUS INTEGRATION SITE 1 (StBMI1). This striking phenotype represents a classic example of modulation of plant architecture and developmental plasticity. Differentiation of a stolon to a tuber or a shoot under in vitro or in vivo conditions symbolizes another example of organ-level plasticity and dual fate acquisition in potato. Stolon-to-tuber transition is governed by SD photoperiod, mobile RNAs/proteins, phytohormones, a plethora of small RNAs and their targets. Recent studies show that polycomb group proteins control microRNA156, phytohormone metabolism/transport/signaling and key tuberization genes through histone modifications to govern tuber development. Our comparative analysis of differentially expressed genes between the overexpression lines of StMSI1, StBEL5 (BEL1-LIKE transcription factor [TF]), and POTATO HOMEOBOX 15 TF revealed more than 1,000 common genes, indicative of a mutual gene regulatory network potentially involved in the formation of aerial and belowground tubers. In this review, in addition to key tuberization factors, we highlight the role of photoperiod and epigenetic mechanism that regulates the development of aerial and belowground tubers in potato.

Historical overview of long-distance signalling in plants - Kondhare, Kirtikumar R.; Patil, Nikita S.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Be it a small herb or a large tree, intra- and intercellular communication and long-distance signalling between distant organs are crucial for every aspect of plant development. The vascular system, comprising xylem and phloem, acts as a major conduit for the transmission of long-distance signals in plants. In addition to expanding our knowledge of vascular development, numerous reports in the past two decades revealed that selective populations of RNAs, proteins, and phytohormones function as mobile signals. Many of these signals were shown to regulate diverse physiological processes, such as flowering, leaf and root development, nutrient acquisition, crop yield, and biotic/abiotic stress responses. In this review, we summarize the significant discoveries made in the past 25 years, with emphasis on key mobile signalling molecules (mRNAs, proteins including RNA-binding proteins, and small RNAs) that have revolutionized our understanding of how plants integrate various intrinsic and external cues in orchestrating growth and development. Additionally, we provide detailed insights on the emerging molecular mechanisms that might control the selective trafficking and delivery of phloem-mobile RNAs to target tissues. We also highlight the cross-kingdom movement of mobile signals during plant-parasite relationships. Considering the dynamic functions of these signals, their implications in crop improvement are also discussed.
Keywords: Long-distance signalling; mobile RNAs; phloem; plasmodesmata; RNA-binding proteins; small RNAs

Polycomb group methyltransferase StE(z)2 and deposition of H3K27me3 and H3K4me3 regulate the expression of tuberization genes in potato - Kumar, Amit; Kondhare, Kirtikumar R.; Malankar, Nilam N.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Polycomb repressive complex (PRC) group proteins regulate various developmental processes in plants by repressing target genes via H3K27 trimethylation, and they function antagonistically with H3K4 trimethylation mediated by Trithorax group proteins. Tuberization in potato has been widely studied, but the role of histone modifications in this process is unknown. Recently, we showed that overexpression of StMSI1, a PRC2 member, alters the expression of tuberization genes in potato. As MSI1 lacks histone-modification activity, we hypothesized that this altered expression could be caused by another PRC2 member, StE(z)2, a potential H3K27 methyltransferase in potato. Here, we demonstrate that a short-day photoperiod influences StE(z)2 expression in the leaves and stolons. StE(z)2 overexpression alters plant architecture and reduces tuber yield, whereas its knockdown enhances yield. ChIP-sequencing using stolons induced by short-days indicated that several genes related to tuberization and phytohormones, such as StBEL5/11/29, StSWEET11B, StGA2OX1, and StPIN1 carry H3K4me3 or H3K27me3 marks and/or are StE(z)2 targets. Interestingly, we observed that another important tuberization gene, StSP6A, is targeted by StE(z)2 in leaves and that it has increased deposition of H3K27me3 under long-day (non-induced) conditions compared to short days. Overall, our results show that StE(z)2 and deposition of H3K27me3 and/or H3K4me3 marks might regulate the expression of key tuberization genes in potato.
Keywords: ChIP-sequencing; Epigenetics; PcG; photoperiod; polycomb repressive complex; potato tuberization; short-day; Solanum tuberosum; StE(z)2

Mobile RNAs and proteins: impacts on plant growth and productivity - Kondhare, Kirtikumar R.; Bhide, Amey J.; Banerjee, Anjan K. (Journal of Experimental Botany, 2025)
Short- and long-distance mobile signals (mobile RNAs and proteins) are integral parts of the local and systemic communications that coordinate various physiological processes at the whole-plant level and have far-reaching impacts on plant productivity. In this review, we aim to provide a comprehensive description of the integral roles of these mobile signals in controlling phenotypic traits and plant productivity. We describe how key mobile RNAs (mRNAs, small RNAs, and long non-coding RNAs) and proteins (including RNA-binding proteins) function as vital regulators of multi-faceted aspects of phenotypic traits that ultimately govern plant productivity, such as the formation of the shoot apical meristem, leaf morphology, root architecture, flowering, ripening of fleshy fruits, tuberization, crop yield, and abiotic stress responses. We also describe recent advances in the study of macromolecular transport mechanisms, such as cyclophilin-mediated transport and extracellular vesicle-based signal delivery, as well as the identification of novel signature motifs on mobile RNAs. In addition, we consider the discovery of new mobile signals and highlight how these signals can potentially be explored with advanced biotechnological interventions, virus-induced flowering, genome-editing tools, and emerging breeding approaches (e.g. the xenia-based mobile RNA delivery system for fleshy fruits) with the aim of designing strategies for enhancing valuable phenotypic traits and improving plant productivity. Mobile RNAs and proteins act as key regulators of shoot apical meristem development, leaf morphology, root architecture, flowering, fleshy fruit ripening, tuberization, yield, and responses to abiotic stresses in plants.
Keywords: Long non-coding RNA; mobile protein; mobile RNA; plant productivity; RNA-binding protein; small RNA